Business Feasibility Study Analysis for Iced Tea MSMEs (First) Reviewed from a Halal Perspective - Devi Triana (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2025)
The purpose of this study is to investigate and analyze the development of the First Ice Tea business, focusing on its business feasibility and halalness. The population used in this study was all First Ice Tea businesses in the Lamongan area, East Java. The data collection methods used include observation and literature study. Data analysis was carried out descriptively and qualitatively using literature studies. The results of the analysis show that from a financial point of view, the First Ice Tea business is feasible to be developed more widely